HUBUNGAN OPTIMISME DENGAN PSYCHOLOGICAL WELL-BEING PADA PENDERITA DIABETES MELITUS TIPE DUA - Putra, Denny; Heny, Heny (Noetic Psychology, 2015)
Abstract - This research aimed to know the correlation of optimism and psychological well-being on people who live with diabetes mellitus type II. The participants in this research involved 33 people who has been diagnosed with diabetes mellitus type two for at least one year, age ranged between 40-75 years old and in recovery process. The method of this research was snowball sampling. This research used optimism and psychological well-being scale. Optimism scale consisted of three dimensional according to Seligmanâs theory and psychological well-being scale was adapted by six dimensions of psychological well-being according to Ryffâs theory. Data analysis was conducted with Pearson Product Moment correlation technique and showed r = 0,779 (p < 0,05) which means the hypothesis of this research is proved. This means that there is a positive correlation between optimism and psychological well-being on people who live with diabetes mellitus type two.Keywords: Diabetes Mellitus Type II, Optimism, Psychological Well-being Â Â